Single Index Model in Optimal Portfolio Formation On Stock Index LQ 45 - Maryam Nadir Maryam; A Ratna Sari Dewi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
The purpose of this study is to analyze the formation of an optimal stock portfolio and provide the expected rate of return and minimum portfolio risk. This type of research is descriptive with a quantitative approach. The data used in this study is secondary data, consisting of closing prices, market index (LQ45 index), seven-day repo rate, beta and alpha for the periods June 2019-June 2020 and June 2020-June 2021. The data analysis method uses Microsoft Excel program to calculate LQ45 stock index in optimal portfolio formation. The results of the study show that there are seven stocks that perform well and form an optimal portfolio, which can be sorted by stock performance, namely: MIKA (44%); JPFA (24%); ITMG (12%); INKP (11%); INDF (6%); PGAS (1%), and PTPP (2%). which produces an expected portfolio return of 13.00% and a portfolio risk level of 19.22%. Of the ten sample companies used in the study, there were three issuers that were not optimal, namely:INTP;MNCN;and PTBA, due to the value of ERB C.